A method for improving the plasticity of powder metallurgy titanium alloy

Through step -by -step heat treatment technology, the problem of poor plastic plasticity of high -oxygen content titanium alloy has been solved, and the high intensity and high extension rate of titanium alloys are realized. It is suitable for large -scale production and overcomes the complex process and high cost of existing technology.

CN114029489BActive Publication Date: 2025-01-28HUNAN INJECTION HIGH-TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111365649.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-18
Publication Date
2025-01-28
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

High oxygen content leads to a significant reduction in the plasticity and toughness of powder metallurgical titanium alloys, limiting their application in aerospace and other fields.

Method used

Adopting step -by -step heat treatment technology, including vacuum heat treatment, heating temperature and warm -preservation and furnace cold treatment, optimizing process parameters to improve the extension of titanium alloy.

Benefits of technology

The extension rate of high oxygen content titanium alloy is significantly increased, reaching more than 15%, while maintaining high strength and density, solving the problems of complex process, high cost, and increasing plasticity in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114029489B_ABST
    Figure CN114029489B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for improving the plasticity of powder metallurgy titanium alloy, wherein titanium alloy powder is prepared according to the designed composition, and titanium alloy products are obtained through molding, sintering densification and heat treatment in sequence. Compared with the prior art, the step-by-step heat treatment technology is adopted to greatly improve the elongation of high-oxygen powder metallurgy titanium alloy, and the method has the advantages of excellent comprehensive performance, high production efficiency, and easy batch production, which can well meet commercial needs and is very suitable for preparing titanium alloy products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the plasticity of a titanium alloy, in particular to a method for improving the plasticity of a powder metallurgy titanium alloy. Background Art

[0002] Titanium and titanium alloys have low density, high specific strength, low thermal expansion coefficient, and high temperature resistance, making them ideal aerospace materials. Due to their good corrosion resistance and biocompatibility, they have become ideal materials for the navigation, petrochemical, medical and other industries, and are known as "modern metals", "third metals", "strategic metals", etc. Titanium alloys produced by forging have excellent performance, but the process is complex, the yield is low, the product cost is high, and it is difficult to obtain products with complex shapes; although the casting method can obtain components with complex structures at a low cost, the casting defects in the casting process lead to low product performance; powder metallurgy technology can achieve powder densification of complex structural parts in a relatively short time, and has superior performance, which can reach the level of forgings. The material utilization rate of this method exceeds 90%, making this technology a special concern of the aviation industry at home and abroad.

[0003] Since titanium has a strong affinity for impurities such as carbon, nitrogen, and oxygen, this affinity will be further aggravated in the powder state, and impurity elements, especially oxygen, seriously affect the density and mechanical properties of sintered titanium and its alloys. Oxygen forms interstitial solid solutions in titanium, produces lattice distortion, and has an obstructive effect on dislocations moving on the slip plane, thereby increasing strength. 0.05wt.% of oxygen can increase the tensile strength of titanium by 50~60MPa, but when it exceeds a certain amount, its plasticity, toughness and impact strength will be greatly reduced. When the oxygen content exceeds 0.3wt.%, the elongation of the titanium alloy is less than 5%, and when the oxygen content reaches 0.5wt.%, the elongation is reduced to less than 2%. This greatly hinders the application and development of powder metallurgy titanium alloys. Developing a method to improve the plasticity of powder metallurgy titanium alloys is an important and urgent topic.

[0004] Zhao Taiyang of Chang'an University proposed a high-strength, high-plasticity powder metallurgy titanium alloy and its processing method. The high-oxygen ingot was subjected to three-upsetting and three-drawing forging, three-upsetting and three-drawing forging, bar rolling and annealing heat treatment to obtain a heterogeneous layered multi-level second phase structure, which enables the alloy to have good high strength and high plasticity matching; the high-strength, high-plasticity powder metallurgy titanium alloy of the present invention has a heterogeneous layered multi-level second phase structure inside, and the layered structure in the heterogeneous layered fine-grained structure can enhance the strength of the alloy structure, and the layered structure can accommodate strain, so that the alloy maintains high toughness and high plasticity (CN112725713A). Guo Ruipeng of Taiyuan University of Technology disclosed a step-by-step hot isostatic pressing preparation method for high-performance powder metallurgy titanium alloy. First, the package containing titanium alloy powder is preformed at 850-900℃ and >100MPa pressure, and then formed at 920-970℃ and >100MPa pressure. The step-by-step hot isostatic pressing process can effectively break the oxide film on the surface of titanium alloy powder, improve the stability of the microstructure of powder metallurgy titanium alloy, and the volume fraction of equiaxed crystals can be continuously adjusted between 20% and 60%, thereby realizing the organization regulation of powder components; at the same time, it can significantly improve the plasticity and high-cycle fatigue performance of powder metallurgy titanium alloy (CN111347045A). Zhao Zibo of the Institute of Metal Research, Chinese Academy of Sciences, disclosed a high-temperature, high-strength titanium alloy and its processing method. The alloy material can be obtained by smelting and powder metallurgy sintering, and then the forging product is obtained by combining thermal deformation and heat treatment processes. The forgings prepared by the above process are dual-state structures. The material has high strength and good plasticity in the range of room temperature to 700°C. It can be used to make key aerospace components for long-term use at 600-700°C, and can also be used for short-term use of heat-resistant structural parts such as spacecraft at 700-750°C (CN112195364A). Although these methods have improved the elongation to a certain extent, they all have defects such as complex process, high cost, and no obvious improvement in plasticity, making them difficult to industrialize. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a method for improving the plasticity of powder metallurgy titanium alloy, and adopts a step-by-step heat treatment technology to greatly improve the elongation of high oxygen content (0.3-0.5wt.%) titanium alloy blank. This method has excellent performance, simple process, and is suitable for large-scale production, overcoming the shortcomings of the above-mentioned process.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention discloses a method for improving the plasticity of a powder metallurgy titanium alloy, comprising the following steps: subjecting the titanium alloy powder to molding, sintering densification and heat treatment in sequence to obtain a titanium alloy product;

[0008] The oxygen content of the sintered titanium alloy is 0.3-0.5wt.%;

[0009] The heat treatment process is performed with a vacuum degree of less than or equal to 10 -2 Pa, first heat up to 50-100℃ below the β phase transition point at 5-10℃ / min and keep warm for 1-4 hours, then furnace cool to 200-300℃ below the β phase transition point, keep warm for 10-30min, and finally air cool to room temperature;

[0010] The elongation of the titanium alloy product is greater than or equal to 15%.

[0011] As a preferred embodiment, the present invention provides a method for improving the plasticity of powder metallurgy titanium alloy, wherein the titanium alloy powder is prepared by one of a hydrogenation deoxidation method, a gas atomization method, and a plasma rotating electrode method.

[0012] As a preferred embodiment, the present invention provides a method for improving the plasticity of a powder metallurgy titanium alloy, wherein the grade of the titanium alloy powder is any one of α+β type dual-phase titanium alloys TC4, TC6, TC8, TC9, TC11, TC15-TC21.

[0013] As a preferred embodiment, the present invention provides a method for improving the plasticity of a powder metallurgy titanium alloy, wherein the molding process is any one of compression molding, cold isostatic pressing, and injection molding.

[0014] As a preferred embodiment, the present invention provides a method for improving the plasticity of powder metallurgy titanium alloy, wherein the molding pressure of the compression molding is 300~600MPa, and the holding time is 30~60min; the molding pressure of the cold isostatic pressing is 300~500MPa, and the holding time is 30~50min; the injection temperature of the injection molding is 120~150°C and the injection pressure is 70~130MPa.

[0015] As a preferred embodiment, the present invention provides a method for improving the plasticity of a powder metallurgy titanium alloy, wherein the sintering treatment is any one of vacuum sintering, hot isostatic pressing sintering, and plasma discharge sintering.

[0016] As a preferred embodiment, the present invention provides a method for improving the plasticity of powder metallurgy titanium alloy, wherein the vacuum degree of vacuum sintering is less than or equal to 10 -3 Pa, the sintering temperature is 1200~1300℃, and the holding time is 1~4h; the protective atmosphere of the hot isostatic pressing sintering is argon, the sintering temperature is 900~1000℃, the holding time is 0.5~2h, and the holding pressure is 100~300MPa; the protective atmosphere of the plasma discharge sintering is argon, the sintering temperature is 900~1000℃, the holding time is 20~40min, and the holding pressure is 50~150MPa.

[0017] As a preferred embodiment, the present invention provides a method for improving the plasticity of a powder metallurgy titanium alloy, wherein the tensile strength of the titanium alloy product is greater than or equal to 850 MPa, and the porosity is less than or equal to 3%.

[0018] Principles and advantages

[0019] In order to solve the problem that the sintered titanium alloy blank has poor plasticity (1-4%) due to high oxygen content, the present invention uses a step-by-step heat treatment technology to greatly improve its elongation for the first time, and does not significantly deteriorate the strength and density of the product, thereby obtaining a titanium alloy product with superior performance. During the technical development process, the present invention attempted to adopt only a one-step heat treatment solution, but no matter how it was optimized, the performance of the obtained product was still unsatisfactory. On this basis, the inventor further tried to adopt a step-by-step heat treatment process and found that after the process parameters were optimized, the performance of the obtained product was significantly improved.

[0020] The final performance of titanium alloy is determined by the morphology of microstructure. Different organizations correspond to different mechanical properties, and the microstructure morphology mainly depends on the chemical composition and preparation process of the alloy. When the chemical composition remains basically unchanged, the final performance of titanium alloy is determined by the preparation process. The sintered structure of two-phase titanium alloy is Widmanstatten structure, which is composed of α phase cluster + α phase grain boundary + interlayer β phase. Because its original β grain is coarser than other types of organization and there are continuous α grain boundaries, its plasticity is low, generally around 5~10%. However, when the oxygen content exceeds 3000ppm, or even reaches 5000ppm, since oxygen is an effective α phase stabilizing element, on the one hand, the increase in oxygen content can promote the precipitation of Ti3Al in the grain or on the grain boundary, and on the other hand, it can produce fine needle-shaped α phase in the β phase. These two aspects lead to a significant reduction in the plasticity of titanium alloy.

[0021] Heat treatment technology has become an indispensable method to change the structure of titanium alloy and improve its mechanical properties. The step-by-step heat treatment technology consists of a first heating, a second heat preservation and a second furnace cooling process. Specifically, the titanium alloy sintered embryo is placed in a vacuum heat treatment furnace and the vacuum degree is less than or equal to 10 -2Pa environment, firstly, the temperature is raised to 50-100°C below the β phase transformation point at 5-10°C / min and kept for 1-4 hours, then furnace cooled to 200-300°C below the β phase transformation point, kept for 10-30 minutes, and finally air cooled to room temperature. Heating to 50-100°C below the β phase transformation point and keeping warm for a certain period of time is to transform as many needle-shaped α phases as possible into β phases, and Al atoms in the Ti3Al phase diffuse into the matrix to reduce the number of this second phase as much as possible, and then reducing 100-200°C and continuing furnace cooling for a period of time is to obtain more phase transformation diffusion time without increasing the grain size, and finally rapid cooling is performed to retain the high-temperature structure. After distributed heat treatment, the Ti3Al phase and the needle-shaped α phase are basically eliminated, and the grain size does not grow significantly, which is the reason why the plasticity of the high-oxygen titanium alloy is improved after heat treatment. The present invention has determined the process parameters of step-by-step heat treatment through a large number of experiments. Under the above process parameters, titanium alloy products with excellent performance can be obtained.

[0022] The present invention adopts a step-by-step heat treatment technology to prepare a powder metallurgy titanium alloy product with excellent performance, simple process and suitable for large-scale production. Compared with the prior art, the present invention has the following advantages:

[0023] 1) Excellent performance. The elongation is more than 50% better than similar products;

[0024] 2) The process is simple. It does not involve complicated processes such as thermal deformation processing;

[0025] 3) Easy to mass produce. The production efficiency is 2~3 times that of existing production technology.

[0026] In summary, the present invention adopts step-by-step heat treatment technology to improve the plasticity of high-oxygen content titanium alloys, reduce the production process, and has the advantages of excellent comprehensive performance, high production efficiency, and easy mass production. It solves the problems of low product performance, low production efficiency, and high cost in the prior art, and can well meet the needs of powder metallurgy titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope photo of a powder metallurgy titanium alloy product. DETAILED DESCRIPTION

[0028] The method of the present invention is further described below with reference to three examples.

[0029] Titanium alloy powder is prepared according to the designed composition, and titanium alloy products are obtained through molding, sintering densification and heat treatment in sequence.

[0030] Embodiment 1:

[0031] A method for improving the plasticity of powder metallurgy titanium alloy, the process is as follows:

[0032] A. Powder preparation: TC4 titanium alloy powder was prepared by gas atomization method;

[0033] B. Molding process: put the weighed raw material powder into the mold, use 400MPa molding pressure to maintain pressure for 45min to obtain the blank;

[0034] C. Sintering densification: put the blank into a hot isostatic press and perform densification treatment under the protection of argon. The sintering temperature is 1000℃, the holding time is 1h, and the oxygen content of the sintered blank is 0.35wt.%;

[0035] D. Heat treatment: In the vacuum heat treatment furnace, the vacuum degree is less than or equal to 10 -2 Pa, firstly, the temperature was raised to 50℃ below the β phase transition point at 5℃ / min and kept at that temperature for 2 hours, then furnace-cooled to 200℃ below the β phase transition point, kept at that temperature for 10 minutes, and finally air-cooled to room temperature;

[0036] E. Performance testing: The mechanical properties were tested and the results were as follows: tensile strength 872MPa, elongation 15.5%.

[0037] Embodiment 2:

[0038] A method for improving the plasticity of powder metallurgy titanium alloy, the process is as follows:

[0039] A. Powder preparation: TC21 titanium alloy powder was prepared using a plasma rotating electrode method;

[0040] B. Molding process: put the weighed raw material powder into the bag of the cold isostatic press, use 400MPa molding pressure to maintain pressure for 35min to obtain the blank;

[0041] C. Sintering densification: Place the blank into a plasma discharge machine and perform densification treatment under the protection of argon gas. The sintering temperature is 1000°C, the holding time is 25 minutes, and the oxygen content of the sintered blank is 0.4wt.%;

[0042] D. Heat treatment: In the vacuum heat treatment furnace, the vacuum degree is less than or equal to 10 -2 Pa, firstly, the temperature was raised to 100°C below the β phase transition point at 5°C / min and kept at that temperature for 1.5 hours, then furnace-cooled to 250°C below the β phase transition point, kept at that temperature for 20 minutes, and finally air-cooled to room temperature;

[0043] E. Performance testing: The mechanical properties were tested and the results were as follows: tensile strength 903MPa, elongation 16.2%.

[0044] Embodiment 3:

[0045] A method for improving the plasticity of powder metallurgy titanium alloy, the process is as follows:

[0046] A. Powder preparation: TC11 titanium alloy powder was prepared by hydrogenation deoxidation method;

[0047] B. Molding process: The weighed raw material powder is mixed with a binder to form a feed material, and a blank is obtained on an injection molding machine. The injection temperature is 120°C and the injection pressure is 110MPa;

[0048] C. Sintering densification: After degreasing, the blank is placed in a vacuum sintering furnace for densification treatment in a vacuum environment with a vacuum degree of less than or equal to 10 -3 Pa, sintering temperature is 1250℃, holding time is 2h, oxygen content of sintered embryo is 0.43wt.%;

[0049] D. Heat treatment: In the vacuum heat treatment furnace, the vacuum degree is less than or equal to 10 -2 Pa, firstly, the temperature was raised to 100°C below the β phase transition point at 10°C / min and kept at that temperature for 2 hours, then furnace-cooled to 200°C below the β phase transition point, kept at that temperature for 20 minutes, and finally air-cooled to room temperature;

[0050] E. Performance testing: The mechanical properties were tested and the results were as follows: tensile strength 856MPa, elongation 15%.

[0051] Series Comparative Example 1:

[0052] Comparative experiment Heat treatment temperature Insulation time Experimental Results 1 50℃ above β phase transition point 1.5h The first holding temperature is higher than the β phase transition point, and the grain size is too large. The mechanical properties are tested and the results are as follows: tensile strength 825MPa, elongation 9% 2 200℃ below β phase transition point 1.5h The first holding temperature is 200℃ lower than the β phase transformation point. The low temperature is not conducive to the diffusion and elimination of the needle-shaped α phase and Ti3Al phase. The mechanical properties are tested and the results are as follows: tensile strength 845MPa, elongation 7% 3 350℃ below β phase transition point 20min The second holding temperature is lower than the β phase transformation point of 350℃. The furnace cooling time is too long, and other second phases may precipitate. The mechanical properties are tested and the results are as follows: tensile strength 846MPa, elongation 8% 4 250℃ below β phase transition point 1.5h The second holding temperature is too long, the second phase may reappear and the grain size grows. The mechanical properties are tested and the results are as follows: tensile strength 838MPa, elongation 6%

[0053] Except for the conditions indicated above, other conditions in Comparative Example 1 are consistent with those in Example 2.

[0054] Series Comparative Example 2

[0055] The only difference from Example 2 is that only the first heat treatment is retained, that is, single-stage heat treatment. The mechanical properties are tested and the results are as follows: tensile strength 844MPa, elongation 4%. This may be due to the reappearance of the second phase during furnace cooling.

[0056] From the above comparison, it can be seen that too high or too low heat treatment temperature, holding time and other process parameters will cause product defects and affect performance.

[0057] The above-described examples are only preferred implementation methods of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. Other equivalent changes, modifications, substitutions and combinations made in accordance with the principles and contents of the present invention still fall within the scope of protection of the present invention.

Claims

1. A method for improving the plasticity of powder metallurgy titanium alloy, characterized in that: The following steps are involved: The titanium alloy powder is subjected to molding treatment, sintering densification and heat treatment in sequence to obtain a titanium alloy product; The molding process is any one of compression molding, cold isostatic pressing, and injection molding; The oxygen content of the sintered titanium alloy is 0.3-0.5wt.%; The heat treatment process is performed with a vacuum degree of less than or equal to 10 -2 Pa, firstly heat up to 50-100℃ below the β phase transition point at 5-10℃ / min and keep it at that temperature for 1-4 hours, then furnace cool to 200-300℃ below the β phase transition point, keep it at that temperature for 10-30min, and finally air cool to room temperature; The elongation of the titanium alloy product is greater than or equal to 15%.

2. A method for improving the plasticity of powder metallurgy titanium alloy according to claim 1, characterized in that; The titanium alloy powder is prepared by one of a hydrogenation deoxidation method, a gas atomization method and a plasma rotating electrode method.

3. A method for improving the plasticity of powder metallurgy titanium alloy according to claim 1, characterized in that; The grade of the titanium alloy powder is any one of α+β type dual phase titanium alloy TC4, TC6, TC8, TC9, TC11, TC15-TC21.

4. A method for improving the plasticity of powder metallurgy titanium alloy according to claim 1, characterized in that; The molding pressure of the compression molding is 300-600MPa, and the holding time is 30-60min; the molding pressure of the cold isostatic pressing is 300-500MPa, and the holding time is 30-50min; the injection temperature of the injection molding is 120-150°C, and the injection pressure is 70-130MPa.

5. The method for improving the plasticity of powder metallurgy titanium alloy according to claim 1, characterized in that: The sintering process is any one of vacuum sintering, hot isostatic pressing sintering and plasma discharge sintering.

6. A method for improving the plasticity of powder metallurgy titanium alloy according to claim 5, characterized in that; The vacuum degree of the vacuum sintering is less than or equal to 10 -3 Pa, the sintering temperature is 1200-1300°C, and the holding time is 1-4h; the protective atmosphere of the hot isostatic pressing sintering is argon, the sintering temperature is 900-1000°C, the holding time is 0.5-2h, and the holding pressure is 100-300MPa; the protective atmosphere of the plasma discharge sintering is argon, the sintering temperature is 900-1000°C, the holding time is 20-40min, and the holding pressure is 50-150MPa.

7. A method for improving the plasticity of powder metallurgy titanium alloy according to claim 1, characterized in that; The tensile strength of the titanium alloy product is greater than or equal to 850 MPa, and the porosity is less than or equal to 3%.

Citation Information

Patent Citations

  • Step-by-step hot isostatic pressing preparation method of high-performance powder metallurgy titanium alloy

    CN111347045A

  • High-temperature and high-strength titanium alloy and processing method thereof

    CN112195364A

  • High-strength and high-plasticity powder metallurgy titanium alloy and machining method thereof

    CN112725713A

  • High-strength beta Ti alloy preparation method

    CN113430409A

  • α+&bgr; TYPE TITANIUM ALLOY AND METHOD FOR PRODUCING THE ALLOY

    JP2015101749A